Pengaruh Jumlah Alternatif Jawaban dan Teknik Penskoran terhadap Reliabilitas Tes - Yoga Budi Bhakti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2015)
This study aimed to determine the effect of the number of alternative answers and scoring techniques to reliability test. Forms of this test includes multiple choice test three answer choice and multiple choice test four answer choices with penalty scoring techniques (Punishment Score) and scoring techniques compensation (Reward Score). The method uses the experiment, while the designused istreatment bylevel 2 x 2. Research hypotheses were tested using two way analysis of variance (ANOVA). The result concluded that: (1) reliability tests with three multiple choice answer options is higher than the multiple choice test four answer choices, (2) reliability tests with scoring techniques penalty higher than the reliability of the technique of scoring compensation, and (3) No interaction between the number of alternative answers to the scoring technique. The results of this study can be considered for the teacher to give test using a form of multiple choice test three answer choice and multiple choice test four answer choices test scoring with a penalty techniques. Keywords : reliability, scoring techniques, alternative answers.